2021
DOI: 10.1177/02537176211022571
|View full text |Cite
|
Sign up to set email alerts
|

Dengue and Psychiatry: Manifestations, Mechanisms, and Management Options

Abstract: Dengue is an arboviral infection endemic in tropical countries. Neurological sequelae to dengue infection are not uncommon, and psychiatric manifestations are increasingly reported. This narrative review aims to present the varied manifestations, postulated mechanisms, and the available treatment options for psychiatric morbidity associated with dengue. The evidence available from eight observational studies is summarized in this review. Depression and anxiety are noted to be prevalent during both the acute an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 65 publications
(150 reference statements)
0
16
0
Order By: Relevance
“…He also developed neurological manifestations. Transient psychological disturbance is often seen in patients with MIS-C due to COVID-19 [18], and dengue [19].…”
Section: Discussionmentioning
confidence: 99%
“…He also developed neurological manifestations. Transient psychological disturbance is often seen in patients with MIS-C due to COVID-19 [18], and dengue [19].…”
Section: Discussionmentioning
confidence: 99%
“…This cohort study’s findings support those of previous research suggesting a potential association between dengue fever and neurological and psychiatric complications, especially in individuals older than 60 years. Although prior case reports and smaller studies 4 , 5 noted the neurotropic nature of the dengue fever virus, this study stands out due to its extensive scale and use of long-term, comprehensive national health data, which may avoid selection bias inherent in smaller datasets. 6 The study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 Apart from possible direct invasion of dengue fever virus to the neurological system, the disease has been reported to be associated with neurological complications probably attributable to autoimmune reactions and metabolic alterations. 3 Several studies 4 , 5 have found an association between dengue fever and neurologic and psychiatric disorders, including anxiety and depression symptoms. This retrospective nationwide cohort study attempted to further scrutinize the association between dengue fever and risk of subsequent neurological or psychiatric complications.…”
Section: Introductionmentioning
confidence: 99%
“…This epigenetic modification is important for investigating mental health issues related to dengue infection. Various HDAC inhibitors like valproate, quetiapine, or carbamazepine are prescribed for treatment as HDAC/Dnmt inhibitors [ 28 ]. Comprehensive transcriptome analysis identified that DENV proteins interact with host genes (CCR10, CNG7, PLXNA3) and lncRNAs (CTBP1-AS, MAFG-AS1) engaged in various biological processes, such as the immune response, inflammation, and the cell cycle, as illustrated in Fig.…”
Section: Denv and The Host Epigenetic Machinerymentioning
confidence: 99%
“…3 DENV and host epigenetic regulation: A DENV infection results in cytokine storm and leads to oxidative stress conditions in host cell, activating histone deacetylase (HDAC). HDAC activity condenses the chromatin and slows down the host transcription processes [ 28 ]. B DENV protein interacts with various host cellular genes/lnCRNAs and results in m6A RNA methylation.…”
Section: Denv and The Host Epigenetic Machinerymentioning
confidence: 99%